posted by .

Use the Pythagorean identity to show that the double angle formula for cosine can be written as
a) cos2x = 1 - 2sin^2x
b) cos2x = 2cos^2x - 1

sin^2x+ cos^2x=1
cos^2x+ sin^2x-2sin^2x=1-2sin^2x
cos^2x-sin^2x=1-2sin^2x
cos(2x)=1-2sin^2x

## Similar Questions

1. ### Trigonometry

Need help solving problems using the Trigonometric Identities: 8cos^4 thet=cos4theta+4cos2theta+3 I am a bit unsure how to solve it. I am aware that the first step I must take is to simplify the problem and then use the Product to …
2. ### Math - Trig - Double Angles

Prove: sin2x / 1 - cos2x = cotx My Attempt: LS: = 2sinxcosx / - 1 - (1 - 2sin^2x) = 2sinxcosx / - 1 + 2sin^2x = cosx / sinx - 1 = cosx / sinx - 1/1 = cosx / sinx - sinx / sinx -- Prove: 2sin(x+y)sin(x-y) = cos2y - cos2x My Attempt: …
3. ### math

the problem is 2cos^2x + sinx-1=0 the directions are to "use an identity to solve each equation on the interval [0,2pi). This is what i've done so far: 2cos^2x+sinx-1=0 2cos^2x-1+sinx=0 cos2x + sinx =0 1 - 2sin^2x + sinx = 0 -2sin^2x+sinx-1=0 …
4. ### trigonometry

Use a compound angle formula for cosine to show that cos2x = cos^2x - sin^2x

Use the Pythagorean Identify to show that the double angle formula for cosine can be written as: cos2x = 2cos^2x - 1
6. ### gr 12. advanced functions

Trig identity Prove: cos2x tan(pie/4 - x) ------- = 1 + sin2x
7. ### Calculus

Solve identity, (1-sin2x)/cos2x = cos2x/(1+sin2x) I tried starting from the right side, RS: =(cos²x-sin²x)/(1+2sinxcosx) =(cos²x-(1-cos²x))/(1+2sinxcosx) and the right side just goes in circle. May I get a hint to start off?
8. ### trig

Use the double angle formula to verify the identity cotxsin2x=1+cos2x
9. ### Trig

If sinx = 1/4 Find the exact value of cos2x I used the formula for double angle identities : cos2x = 1-2sin^2x and got the answer 1/2 The book says the answer is 7/8 How would they get to that conclusion?
10. ### Pre-Calculus

Find all solutions to the equation in the interval [0, 2pi) cos4x-cos2x=0 So,this is what i've done so far: cos4x-cos2x=0 cos2(2x)-cos2x (2cos^2(2x)-1)-(2cos^2(x)-1) No idea what to do next.

More Similar Questions